Endogenous Histoplasma Capsulatum Endophthalmitis in An Immunocompetent Patient. Issue 4 (July 2015) - Schlaen, Ariel; Ingolotti, Mariana; Couto, Cristobal; Jacob, Nestor; Pineda, Gloria; Saravia, Mario
Purpose: To report on a case of Histoplasma capsulatum endogenous endophthalmitis in an immunocompetent patient. Methods: A 30-year-old patient was admitted with floaters and vision impairment of 1 month's duration. He had a history of adrenal insufficiency, together with nasal, septum, and soft palate lesions of 3 months; duration. Culture results from specimens of these lesions were positive for H capsulatum . He was human immunodeficiency virus negative and there was no evidence of immunodepression or history of immunosuppression. Fundus examination revealed multiple fluffy balls with a string of pearls appearance, 2+ vitreous haze, multiple foci of retinochoroiditis inferiorly in the peripheral retina, and a 6-disk area lesion of retinochoroiditis at the superotemporal periphery. Due to poor response to oral itraconazole, a vitrectomy was performed with an intraocular injection of amphotericin B 5 μg/0.1 mL and removal for a vitreous specimen for culture of bacteria and fungi. Results: Vitreous specimen culture of the yeast at 28°C grew a white filamentous fungus colony, which was again cultured in a brain heart infusion agar medium, where it developed hyaline septate hyphae with microconidia and circular macroconidia with double wall, which was stained with a lactophenol dye at microscopic examination. The macroscopic morphology was consistent with H capsulatum . Conclusions: Although endogenous H capsulatum endophthalmitis is a rare entity, it should be considered as a possible etiology even in apparently immunocompetent hosts, especially in patients with history of disseminated disease.